Impact of changes in gdp in the collection of the state of gst by economic sectors PiauÃ - Antonio Walter Gadelha GuimarÃes (2010)
This work aims at analyzing the impact of changes in Gross Domestic Product (GDP) on the collection of VAT in the State of PiauÃ, studying separately the fluctuations of the collections in the primary, secondary and tertiary. Used in developing this work ICMS and GDP data, which were analyzed using econometric regression model for time series with panel data, to identify the elasticities of the PIB variable that will affect the ICMS variable. The results show clearly that the growth rate of the ICMS follows the growth rate of GDP, the total level, and specifically, this behavior was repeated in the secondary and tertiary sectors of the economy of the state of Piaui.